”Catholic Shakespeare?”. A response to Hildegard Hammerschmidt- Hummel’s book - Ernst A.J. Honigmann (Przestrzenie Teorii, 2011)
The text “Catholic Shakespeare?” is a response to the book of Hildegard Hammerschmidt-Hummel titled William Shakespeare – Sein Zeit – Sein Leben – Sein Werk (2003). E.A.J. Honigmann joins the debate about a secret Catholic code in Shakespeare’s plays. The researcher disagrees with some theses, for example with mysterious inscriptions in the English College at Rheims. He also tries to convince that Shakespeare’s Catholicism isn’t that obvious as Hammerschmidt-Hummel says.